Correspondentist truth in kantian practical philosophy, as a criteria for analysis of the fake news phenomenon - de Oliveira, Carlos Moisés (Con-Textos Kantianos. International Journal of Philosophy, 2023)
This article aims to discuss the complex phenomenon of fake news, defining it, establishing its main characteristics and consequences, whether for the individual in their daily lives, as a consequent harm to their education and moral construction, or for society, reflecting on the impacts they can have on large groups. To analyze this issue, we anchor ourselves in Kantian philosophy, using his epistemology to investigate the meaning of truth and how it was articulated in his theoretical corpus; in the practical field, we understand the implication of his concept of truth in law, politics and moral action. As a result, we gained an understanding of the impact of fake news and its ability to create moral chaos, while slowly undermining concepts and institutions indispensable for the maintenance of civilization, as well as the path of reason taking place in history.
Keywords: Fake news; correspondent truth; practical philosophy; moral chaos